Using activity and movement patterns to improve the rate of bait encounter during large-scale aerial baiting for feral cats. Issue 3 (3rd July 2021) - Tiller, Cameron; Fletcher, Jason; Comer, Sarah; Algar, Dave
ABSTRACT: The efficiency of feral predator control can be improved dramatically by adjustments that take into account activity and movement patterns of the predator. These traits were analysed for large samples of feral cats at three sites widely distributed throughout Western Australia to encompass a range of habitat and climatic variables in order to improve methods large-scale aerial baiting control programs. Seventy-eight feral cats were collared with GPS data-logger/radio telemetry collars and predominantly tracked at one-hourly intervals for between 16 and 118 days. There was sufficient difference in the patterns of movement between sites to suggest that aerial baiting programs can benefit greatly by altering current delivery methods to increase the rate of bait encounter by feral cats. Although likely, further testing is required to determine whether these results can be extrapolated to other introduced predators (i.e. introduced canids) to increase the success of control programs for these species.